Offering fleet automation : SmartFleet in the need of smart decisions - Agrawal, Anand M., (SAGE Business Cases., 2018)
In late September 2014, after reviewing the revised financial projection of their new venture, Maui Millan, the CEO and the head of product development, and Mannix Chong, the COO and the head of business development were alarmed. They planned to call their board of advisors to discuss the future of SmartFleet, the new product of the Philippines-based firm called Pahrsek Inc. SmartFleet is a cloud-based fleet management tool that provides enterprise resource planning capability to fleet vehicle operators. For Maui and Mannix, there were numerous challenges ranging from developing a pricing strategy, growing the market as a pioneer in this industry in the Philippines, to proactively managing the potential global competitors who were on the verge of the Philippines market. They were anxious because they knew that only a set of careful, well-thought out and smart decisions could ensure survival and sustainability of this new venture.